The poisons we drink - Baptiste, Bethany (Sourcebooks Fire, 2024)
The Poisons We Drink is a potent YA debut about a world where love potions are weaponized against hate and prejudice, sisterhood is unbreakable, and self-love is life and death. In a country divided between humans and witchers, Venus Stoneheart hustles as a brewer making illegal love potions to support her family. Love potions is a dangerous business. Brewing has painful, debilitating side effects, and getting caught means death or a prison sentence. But what Venus is most afraid of is the dark, sentient magic within her. Then an enemy's iron bullet kills her mother, Venus's life implodes. Keeping her reckless little sister Janus safe is now her responsibility. When the powerful Grand Witcher, the ruthless head of her coven, offers Venus the chance to punish her mother's killer, she has to pay a steep price for revenge. The cost? Brew poisonous potions to enslave D.C.'s most influential politicians. As Venus crawls deeper into the corrupt underbelly of her city, the line between magic and power blurs, and it's hard to tell who to trust...herself included.
Ages 14+
Keywords: Magic; Witches; Poisons; Poisoning; Corruption; Death; Revenge; Dystopias; Aphrodisiacs; Politicians; Young adult fiction; Sorcières - Romans; nouvelles; etc. pour la jeunesse; Poisons - Romans; nouvelles; etc. pour la jeunesse; Corruption - Romans; nouvelles; etc. pour la jeunesse; Vengeance - Romans; nouvelles; etc. pour la jeunesse; Dystopies - Romans; nouvelles; etc. pour la jeunesse; Aphrodisiaques - Romans; nouvelles; etc. pour la jeunesse; Politiciens - Romans; nouvelles; etc. pour la jeunesse; Roman pour jeunes adultes; Witch fiction; Fantasy fiction; Dystopian fiction